Intra-household handling and consumption dynamics of milk in peri-urban informal markets in Tanzania and Kenya: A gender lens - Galiè, Alessandra; Farnworth, Cathy Rozel; Njiru, Nelly; Alonso, Silvia (MDPI, 2021)
Milk, provided it is safe, provides important micronutrients that can combat hidden hunger (undernutrition). Many peri-urban poor people in Tanzania and Kenya use informal markets to purchase milk in order to provide nutritional benefits to their families. Household decision-making processes play an influential role in how much milk to buy and how it is treated. This exploratory qualitative study, conducted in peri-urban Nairobi and Dar es Salaam, examined how access to milk, control over milk handling and safety, and intra-household milk distribution are affected by gender dynamics and by changes in milk availability and price. Focus group discussions with 48 women and 45 men and key informant interviews with 8 men and 8 women, all of whom were parents or caretakers to young children, were conducted. The results indicate that gender roles in milk purchase and handling vary. Generally, providing enough milk is a man’s responsibility, whilst a woman is expected to ensure a nutritious diet. Yet women’s limited decision-making power regarding milk purchase can restrict their ability to provide sufficient milk. Interventions to promote safe milk consumption need to consider gender norms, strengthen intra-household collaborative decision-making, include men in nutrition programming, and increase women’s control over food expenditures.